2015
DOI: 10.1155/2015/958170
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sensor-EnabledEx VivoBioreactor: A New Approach towards Physiological Parameters and Porcine Artery Viability

Abstract: The aim of the present work is to design and construct an ex vivo bioreactor system to assess the real time viability of vascular tissue. Porcine carotid artery as a model tissue was used in the ex vivo bioreactor setup to monitor its viability under physiological conditions such as oxygen, pressure, temperature, and flow. The real time tissue viability was evaluated by monitoring tissue metabolism through a fluorescent indicator “resorufin.” Our ex vivo bioreactor allows real time monitoring of tissue respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Similar considerations have been taken into account by Mundagi et al, who investigated carotid arteries with lengths varying from 8 to 12 cm [2], whereas Piola et al mounted 5 cm long segments in the vessel culture system [14]. Contrary to our assumption, Miyakawa et al introduced saphenous veins with 2 cm each [16].…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Similar considerations have been taken into account by Mundagi et al, who investigated carotid arteries with lengths varying from 8 to 12 cm [2], whereas Piola et al mounted 5 cm long segments in the vessel culture system [14]. Contrary to our assumption, Miyakawa et al introduced saphenous veins with 2 cm each [16].…”
Section: Discussionmentioning
confidence: 62%
“…However, effects of altered flow conditions have only been investigated in human saphenous veins after coronary artery bypass grafting [13]. Mundagi et al also reported on an ex vivo bioreactor that allowed an evaluation of cellular interactions in the carotid artery of pigs under controlled physiologic conditions [2]. Oxygen saturation and temperature have been successfully controlled.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations